Marriage Agreements as Legal Protection of Collective Property - Surbakti, Handayana Br (Al-Ubudiyah: Jurnal Pendidikan dan Studi Islam, 2023)
Marriage is a legal act in which an act contains rights and obligations for the individuals who commit it. In living the life of a household, it is not uncommon for problems to arise which cause disputes between husband and wife and end in divorce. Dissolution of marriage will cause problems, one of which is related to property (assets) in the marriage. This study aims to map the arrangement of the marriage agreement in Law No. 1 of 1974 concerning marriage and to analyze the legal protection of joint assets in the marriage agreement. The type of research used in this study is normative juridical, by collecting data using the literature and applicable laws and regulations. To get the results of this study, the author use descriptive data analysis to describe the nature of the problems studied. The results of this study indicate that the marriage agreement was held at the time or before the marriage took place, the two parties with mutual consent can enter into a written agreement which is legalized by the marriage registrar, after which the contents also apply to third parties as long as the third party is concerned. Legal protection of joint assets with a marriage certificate before the marriage takes place. The deed is made in writing which is legalized by the marriage registration officer, namely the Office of Religious Affairs (Muslim) and Civil Registry (Non-Muslim).